Inklusion von Lehrkräften nach der Flucht Über universitäre Ausbildung zum beruflichen Wiedereinstieg - Kremsner, Gertraud; Proyer, Michelle; Biewer, Gottfried (Verlag Julius Klinkhardt, 2020)
This volume is dedicated to the professional re-entry of teachers with a refugee background into the teaching profession. The book presents the certificate course "Educational Science Basics for Teachers with a Refugee Background" at the University of Vienna and research results on it in detail. Furthermore, the teachers and participants reflect on their experiences with this measure. Challenges and synergies in connection with the implementation of such a course are discussed as well as international perspectives on the requalification of refugee teachers.